EDITORIAL: Reflections on abortion. - Tang Bruigget, Luis (2015)
Life and health are the most precious gifts we have, but many times we do not bother to keep them. The abortion is a drama with various endings. One is the tragedy of abortion and its consequences, that can end the life of women. The issue of abortion from any aspect being studied, is of often conflicting opinions, be they social, family, medical, ethical or moral, because each has a particular concept about the problem.